Resistensi Sosial terhadap Kebijakan Usia Minimal Perkawinan: Analisis Implementasi di Kecamatan Poncokusomo Kabupaten Malang - ahmad yusroni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2025)
Child marriage remains a significant social issue in Indonesia, with profound negative effects on education, health, and socio-economic development. This study aims to analyze the implementation of the minimum marriage age policy in Poncokusumo District, Malang Regency, focusing on the roles of local institutions and societal resistance. Using a qualitative approach grounded in Pressman and Wildavsky’s implementation theory, data was collected through in-depth interviews, document analysis, and field observations. Findings indicate that despite a national decline in child marriage rates, Poncokusumo experiences persistent challenges related to entrenched cultural norms, economic factors, and limited institutional capacity. Multi-actor synergy involving government bodies, religious institutions, and community leaders plays a pivotal role in advancing policy goals. However, significant social resistance necessitates culturally adaptive education and collaborative governance to enhance policy acceptance and effectiveness. The study recommends strengthening institutional resources, fostering cross-sectoral communication, and integrating culturally sensitive outreach strategies. These insights contribute to the literature on context-sensitive policy implementation and offer practical guidance for reducing child marriage in socio-culturally complex settings.